2020
DOI: 10.4081/jlimnol.2020.1912
|View full text |Cite
|
Sign up to set email alerts
|

Diet of tadpoles for five anuran species of northeast Brazil

Abstract: In this study, the diet of tadpoles of five anuran species was described. The species were collected from either lotic or lentic environments in Caatinga and the Atlantic Forest biome of northeast Brazil. The diet of these tadpoles consisted of algae, protozoa, plants, fungi and animals. Diatoms were the most important items within the diet of Leptodactylus natalensis. Trachelomonas, diatoms, Phacus and Scenedesmus were the most important items comprising the diet of Leptodactylus cf. macrosternum. Trachelomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
4
0
3
Order By: Relevance
“…The most remarkable exceptions were the predaceous tadpole of Ceratophryidae, which ate insects, crustaceans and tadpoles (Fabrezi & Cruz, 2020; Vera Candioti, 2005), the bromeliad‐dwelling tadpoles of Scinax littoreus and S. perpusillus , which ate mainly Cyanophyceae and Zygnematophyceae respectively (Sabagh et al, 2012) and the tree hole breeder Trachycephalus cunauaru , which ate mainly conspecific eggs (Schiesari et al, 2003). Tadpoles also had other items besides algae in their guts, however, usually in small proportions, such as fungi (Protázio et al, 2020), testate amoeba (Kloh et al, 2018, 2019; Pollo et al, 2019; Sabagh et al, 2012; Vera Candioti, 2005; Vera Candioti, 2007), insect remains/eggs/larvae (Dutra & Callisto, 2005; Pollo et al, 2019; Protázio et al, 2020; Sabagh et al, 2012), Rotifera, Cilliophora, Nematoda, Crustacea, Oligochaeta (Verburg et al, 2007), pollen (Kloh et al, 2019; Protázio et al, 2020; Sabagh et al, 2012). The proportion of diatoms in tadpole diets may be overestimated because many studies analysed the whole digestive tract and the capsules of diatoms can be identified even after digestion, whereas other items are digested and not seen in posterior portions of the gut (Kloh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most remarkable exceptions were the predaceous tadpole of Ceratophryidae, which ate insects, crustaceans and tadpoles (Fabrezi & Cruz, 2020; Vera Candioti, 2005), the bromeliad‐dwelling tadpoles of Scinax littoreus and S. perpusillus , which ate mainly Cyanophyceae and Zygnematophyceae respectively (Sabagh et al, 2012) and the tree hole breeder Trachycephalus cunauaru , which ate mainly conspecific eggs (Schiesari et al, 2003). Tadpoles also had other items besides algae in their guts, however, usually in small proportions, such as fungi (Protázio et al, 2020), testate amoeba (Kloh et al, 2018, 2019; Pollo et al, 2019; Sabagh et al, 2012; Vera Candioti, 2005; Vera Candioti, 2007), insect remains/eggs/larvae (Dutra & Callisto, 2005; Pollo et al, 2019; Protázio et al, 2020; Sabagh et al, 2012), Rotifera, Cilliophora, Nematoda, Crustacea, Oligochaeta (Verburg et al, 2007), pollen (Kloh et al, 2019; Protázio et al, 2020; Sabagh et al, 2012). The proportion of diatoms in tadpole diets may be overestimated because many studies analysed the whole digestive tract and the capsules of diatoms can be identified even after digestion, whereas other items are digested and not seen in posterior portions of the gut (Kloh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on available studies, diatoms (Bacillariophyta, Bacillariophyceae) were usually the numerically predominant items in the diets of most neotropical tadpoles (e.g. Baffico & Úbeda, 2006; Kloh et al, 2019; Protázio et al, 2020; Santos et al, 2016). The most remarkable exceptions were the predaceous tadpole of Ceratophryidae, which ate insects, crustaceans and tadpoles (Fabrezi & Cruz, 2020; Vera Candioti, 2005), the bromeliad‐dwelling tadpoles of Scinax littoreus and S. perpusillus , which ate mainly Cyanophyceae and Zygnematophyceae respectively (Sabagh et al, 2012) and the tree hole breeder Trachycephalus cunauaru , which ate mainly conspecific eggs (Schiesari et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As dietas dos girinos de cinco espécies, presentes em riachos brasileiros, refletiram a disponibilidade de itens alimentares nos microhabitats que utilizavam, porém alguns itens foram consumidos em proporções maiores, enquanto outros aparentemente foram evitados, sendo a discrepância entre as proporções disponíveis e consumidas maior para algumas espécies do que para outras (por exemplo, Bokermannohyla saxicola ; Kloh et al, 2019). Embora seja amplamente assumido que os girinos são consumidores não seletivos (por exemplo, Dutra & Callisto, 2005; Protázio et al, 2020), os estudos que avaliaram a disponibilidade de alimentos em comparação com o consumo pelos girinos indicam que isto não deve ser considerado uma regra geral (por exemplo, Antoniazzi et al, 2020).…”
Section: Discussionunclassified
“…Apenas dois estudos empregaram análises de isótopos estáveis (Antoniazzi et al, 2020; Huckembeck et al, 2014), uma técnica que dá uma imagem mais realista do que é realmente assimilado pelos girinos. Com base nos estudos disponíveis, as diatomáceas (Bacillariophyta, Bacillariophyceae) foram geralmente os itens numericamente predominantes nas dietas da maioria dos girinos neotropicais (por exemplo, Baffico & Úbeda, 2006; Kloh et al, 2019; Protázio et al, 2020; Santos et al, 2016). As exceções mais notáveis foram o girino predador de Ceratophryidae, que se alimentou de insetos, crustáceos e girinos (Fabrezi & Cruz, 2020; Vera Candioti, 2005), os girinos de Scinax littoreus e S. perpusillus , que se desenvolvem em bromélias e se alimentaram principalmente de Cyanophyceae e Zygnematophyceae, respectivamente (Sabagh et al, 2012) e o girino de Trachycephalus cunauaru , que se desenvolve em buracos de árvores e se alimentou principalmente de ovos conespecíficos (Schiesari et al, 2003).…”
Section: Discussionunclassified
See 1 more Smart Citation